Lost and found - Yttrup, Ginny L. (B&H Pub. Group, 2012)
"Jenna Bouvier is losing everything: beauty, family, and wealth. When her emotionally destructive mother-in-law accuses Jenna of an affair with her spiritual director and threatens to expose them, Jenna also risks losing her reputation as a woman of faith. She must choose between bowing to her mother-in-law's controlling wishes or fighting for what she holds dear. As Jenna loses her life, will she find it? Andee Bell has found exactly what she wanted: fame, fortune, respect, and a special man--Jenna's brother. Despite the success, a secret quells her contentment. As memories torment, Andee can pursue peace in a relationship with God or sabotage herself while taking down the only person she cares about. As Andee finds her life, will she lose it? Moving between San Francisco and the Napa Valley, Jenna and Andee form an unlikely relationship that leads them to a crossroad. They can follow familiar inclinations, or risk it all and walk in faith."--P. [4] of cover.